1998
DOI: 10.1021/la971206p
|View full text |Cite
|
Sign up to set email alerts
|

Study of Liquid Crystal Prewetting Films by Atomic Force Microscopy in Tapping Mode

Abstract: We demonstrate the use of tapping mode atomic force microscopy (TMAFM) for the study of liquid crystal prewetting films spreading on silicon wafers. With AFM, we are able to image the edge of the prewetting film when it spreads on the solid and to obtain images on its surface with a resolution in the nanometer range. As an example, we study the roughness of the film surface: we have observed, in agreement with theoretical predictions, that the undulations of the liquid films follow those of the solid surface (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Contact and tapping AFM modes provide lateral resolution equal to the contact diameter, typically around 1 nm. Tapping mode AFM has indeed been used to image the prewetting layer [11]. However, the perturbation introduced by the contact severely limits the usefulness of the information obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contact and tapping AFM modes provide lateral resolution equal to the contact diameter, typically around 1 nm. Tapping mode AFM has indeed been used to image the prewetting layer [11]. However, the perturbation introduced by the contact severely limits the usefulness of the information obtained.…”
mentioning
confidence: 99%
“…In the smectic-A phase, the dimers form layers spaced by 31.7 Å, with the dimers aligned perpendicular to the layers [10]. Ellipsometry and x-ray reflectivity have been used to study the spreading and structure of macroscopic (in x, y) films of 8CB on silicon wafers [3,11]. It was found that a prewetting film is formed during spreading in the smectic and nematic phases.…”
mentioning
confidence: 99%
“…The spreading of 8CB on silicon wafers has been extensively studied and results in the formation of macroscopic films showing a layered structure. [20][21][22] The height of the steps formed by the different layers is 32 . Deposition of 8CB on a PC nonreflective substrate resulted in a very similar layered structure (Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The AFM has been used to study oscillatory hydration forces between tips and CaCO 3 and BaSO 4 substrates in water (Cleveland et al, 1995). Tapping-mode AFM has also been used in the imaging of liquid droplets and films (Pompe et al, 1998(Pompe et al, , 1999Sheiko et al, 1996;Bardon et al, 1998). In these AFM studies, however, the tip enters in contact with the surface, which makes it difficult to avoid a strong perturbation of the liquid by the imaging tip.…”
Section: Experimental Studies Of Wetting Phenomenamentioning
confidence: 99%
“…In the smectic-A phase, the dimers form layers spaced by 31.7 Å, with the dimers aligned perpendicular to the layers (61). Ellipsometry and X-ray reflectivity have been used to study the spreading and structure of macroscopic (in x, y) films of 8CB on silicon wafers (Bardon et al, 1998(Bardon et al, , 1999. It was found that a prewetting film is formed during spreading in the smectic and nematic phases.…”
Section: Layering Of Liquid Crystalsmentioning
confidence: 99%